THE ROLE AND IMPORTANCE OF HISTORICAL THOUGHT CULTURE IN THE PERCEPTION OF NATIONAL IDENTITY - Shokirov Mubin Rustamovich (Scholar Express Journal, 2022)
This article analyzes the socio-philosophical analysis of the process of deep socio-economic reforms in Uzbekistan, one of the most important features of modern national consciousness, ensuring its coherence with reforms and its impact on ideological changes, the need to renew historical thinking. Some specific aspects of the culture of historical thinking and its importance in understanding the national identity have been studied and relevant conclusions have been given. The issues of creating a fair and objective history, the socio-philosophical foundations of the spirit of loyalty to the Uzbek national values were studied, and future tasks in this regard were discussed. The article is also based on the fact that the ideological struggle of the Uzbek people in the world is aimed at educating a new generation that will make a worthy contribution to the work of national identity
Keywords: Philosophy of history; historical consciousness; historical thinking; national pride